Pengaruh Kemampuan Numerik dan Spasial terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP - Juliyanti Juliyanti; Sudi Prayitno; Amrullah Amrullah; Ketut Sarjana (Griya Journal of Mathematics Education and Application, 2021)
This study aims to determine the effect of numerical and spatial ability on mathematics learning outcomes of students class VIII of SMPN 2 Labuapi. This types of research is ex post facto research with a quantitative approach. The population of this study was students of class VIII SMPN 2 Labuapi. In determining the sample, the probability sampling technique is used with the types of cluster random sampling. The sample in this study were students of class VIII-B SMPN 2 Labuapi totaling 30 people. The data collection techniques used were test and documentation. This research uses statistic descriptive statistical analysis techniques and inferential statistical analysis techniques. The result obtained indicate that there is an influence on numerical and spatial ability on the mathematics learning outcomes of class VIII students of SMPN 2 Labuapi with an effect of 76,6%.